GPCM ANALYSIS OF CONSTRUCTED-RESPONSE ASSESSMENT (CRA): MEASURING ABSTRACTION VIA ANALYTIC CODING - Ocy, Dwi Rismi; Rahayu, Wardani; Sarifah, Iva; Tjalla, Awaluddin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Traditional multiple-choice tests frequently fail to capture the subtle cognitive ability of mathematical abstraction in subjects like trigonometric ratio. The purpose of this study was to create and evaluate a performance-based evaluation tool to gauge students' proficiency with mathematical abstraction in the context of trigonometric ratio. Three constructed-response items made up the instrument, and each one was assessed using a unique analytical rubric that was in line with revised Bloom's taxonomy and abstraction processes. Following person-fit screening, 700 replies from 913 tenth-grade students in six Indonesian high schools were kept. Strong item fit, suitable threshold values, and high discrimination indices were found via Generalized Partial Credit Model (GPCM) analysis, demonstrating the instrument's efficacy in distinguishing between different levels of abstraction. Unidimensionality was confirmed by exploratory factor analysis, which had an excellent model fit and explained 41.0% of the total variance (RMSEA = 0.0301; TLI = 0.9775). Item difficulty levels matched the sample's ability distribution quite well, according to person-item mappings. The construct validity of the analytical rubric was further reinforced by high factor loadings and communalities. Results show that the created tool is theoretically and psychometrically solid, providing a strong means of evaluating Mathematical Abstraction in HOTS. The study demonstrates how GPCM-based analytical scoring may be used to capture complex cognitive performance and guide teaching strategies in accordance with the Merdeka Curriculum.